USAHA FURNITUR ALTERNATIF âDUS DUK DUKâ DENGAN KONSEP RAMAH LINGKUNGAN, DESAIN NUSANTARA, FUNGSIONALIS DAN ERGONOMIS - Wiranata, Angger Diri; Nugroho, Indra Syamsu; Susanto, Muhammad Arif; Anggara, Octiana Dwi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Cardboard is one commodity paper required by almost all people. Modern life now cannot be separated from the paper that most of the wood raw material harvested from the forest trees. So it is conceivable, if the use of paper filled only by the original fiber it will have a direct impact on environmental sustainability. However, a lot of boxes just end up in the trash. On the other hand furniture industries development in Indonesia cannot be separated from the timber material. The development resulted in an ever increasing need for growing including furniture anyway. Thus, there is an opportunity to balance between several waste reduction issues with the need for furniture. Opportunities that can be realized is to make furniture made from cardboard. Products produced furniture has a unique design because it is made of cardboard material that is environmentally friendly and functional design. With this furniture, people can participate in protecting environment. In addition, some textile products backed furniture so that the impression of modern ethnic archipelago remains. Some of the advantages is the furniture can be used as a unique iconic furniture to support a room (interior). This is a market segmentation of Dus Duk Duk, as well as from several professions that use furniture, such as cafe, restaurant, childrens playground, and home. Marketing is done by the system offline and online. The business has great competitiveness and sustainable efforts that can be prospective. Important point about the sustainability of such efforts is to create new jobs for the community.